Anaerobic critical velocity and spring swimming performance in master swimmers - Espada, Mário (2018)
The aims of this study were to determine and analyze the relationship between anaerobic critical velocity (AnCV, m.s-1) in master swimmers and short swimming distances performances. AnCV was determined for twenty four male master swimmers (42.0 ± 7.5 years) based on the performance in 15, 25, and 50 m swimming distances. Data was calculated for each swimmer using the slope of the distance-time relationship and compared with the individual best swimming performance in 100 and 200 m distances. AnCV15-25 (1.25 ± 0.22 m.s-1) was significantly lower than AnCV15-25-50 (1.29 ± 0.23 m.s-1) and AnCV25-50 (1.31 ± 0.23 m.s-1) was significantly faster compared to AnCV15-25 and AnCV15-25-50. All AnCV combinations were strongly correlated with swimming performance in 25, 50 and 100 m front-crawl (above 0.90, p < 0.01), and 25 and 200 m performances in master swimmers (below 0.90, p < 0.01). These findings suggest that AnCV can be used as a race-pace training reference to monitoring and prescribing anaerobic training in master swimmers, a non-invasive and inexpensive method that can estimate parameters normally obtained from blood lactate analysis.